UNETHICAL LEADERSHIP AND KNOWLEDGE SABOTAGE IN THE DIGITAL ERA: THE MEDIATING ROLE OF MORAL DISENGAGEMENT AND THE MODERATING ROLE OF MORAL IDENTITY - Miswanto, Teguh Wijaya; Bastian, Adolf; Junaidi, Junaidi (Jurnal Daya Saing, 2026)
This study investigates the effect of unethical leadership on knowledge sabotage in the digital work environment, with moral disengagement as a mediating variable and moral identity as a moderating variable. Digital transformation has increased organizational dependence on knowledge-sharing systems, but unethical leadership may trigger counterproductive knowledge behaviors. This study employed a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through a structured questionnaire distributed to employees of oil and gas service companies in Riau Province, Indonesia. A total of 272 valid responses were analyzed using SmartPLS. The measurement model was evaluated through outer loading, Average Variance Extracted (AVE), Cronbach’s Alpha, and Composite Reliability. The structural model was assessed using path coefficients, coefficient of determination (R²), effect size (f²), predictive relevance (Q²), as well as mediation and moderation analyses through bootstrapping. The results indicate that unethical leadership has a positive and significant effect on knowledge sabotage and moral disengagement. Moral disengagement significantly affects knowledge sabotage and partially mediates the relationship between unethical leadership and knowledge sabotage. Moral identity has a significant negative direct effect on knowledge sabotage but does not moderate the effect of moral disengagement. These findings contribute to ethical leadership and knowledge management literature in digital organizations.